The Internalization of Local Cultur Literacy through Traditional Games in Elementary Textbooks (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Traditional games are a cultural property of a community entity in a region. The threat of globalization has marginalized traditional games to the point where they can become extinct at any time, so the cultivation of cultural literacy through textbooks about textbooks is important to do in schools. This study aims to describe the internalization of local cultur literacy through traditional games in elementary textbooks. This research is qualitative with a library research design. Data obtained through library materials This is a qualitative study that employs a library research research design or library research. The research implementation used library materials to obtain research sources by limiting the process to library collections without requiring direct research in the field. The data sources used in this study were elementary school thematic textbooks and articles relevant to the research topic. Data collection in this study used the documentation method, namely the process of searching for library data related to the research topic. Data analysis techniques in this study used qualitative techniques with content analysis. This study produced the following descriptions of The Internalization of Local Cultur Literacy through Traditional Games in Elementary Textbooks : concepts, general descriptions, steps to play, and the values contained in traditional games. At least in one thematic book, there are at least 2-3 types of traditional games at each grade level.